FAKTOR SOSIAL YANG MEMPENGARUHI PENINGKATAN PENDAPATAN USAHATANI PADI DI KABUPATEN PASURUAN - Novi Itsna Hidayati; Amanatuz Zuhriyah; Novita Lidyana (Agriculture Faculty of Flores University, 2022)
The Paddy plant is one of the important primary food commodities in Indonesia, Java island is one of the national paddy granaries in Indonesia. As one of the staple ingredients in Indonesia, Paddy rice is also used as a source of livelihood for most people in Indonesia. Sumbersuko Village, located in Pasuruan Regency, Purwosari District, is a village in which the majority of the population works as paddy rice farmers. From this background, the study aims to determine the income level of paddy rice farmers in Sumbersuko Village and to see what factors that influence paddy rice production in Sumbersuko Village. The data used in this study include primary data sources and secondary data sources. The analysis method used is farm income and linear regression. The result of this research is that the average income of rice farmers in Sumbersuko village is around 4,986,054, -IDR per hectare. The factors that significantly influence the area-wide land.